HUBUNGAN KONSEP EKONOMI DAN PENDIDIKAN DALAM PENGEMBANGAN SUMBER DAYA MANUSIA - ROSMINI MADEAMIN (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2008)
Education have the important role in make-up of human resource quality. Education influence fully economic growth a nation. This matter not only because education will have an effect on to productivity, but also will have an effect on to fertilitas society. Education make the human resource more able to quick parts and ready to in face of change in environment work. Therefore, is not surprise if state own the resident with the high education storey;level will have the fast economics growth storey;level